Magistrates without Pedigree: The Consules Suffecti of the Triumviral Age. (7th May 2018) - Pina Polo, Francisco
Abstract: The use of the suffect consulship began to change with Caesar in 45b.c., after a number of decades in which no suffect consul had been elected. The office altered dramatically during the triumviral period. The triumvirs openly made use of the suffect consulship as a means of rewarding loyalty. Many of the suffect consuls, who were no longer elected by the people, but designated in advance by the triumvirs, were homines novi who belonged to previously unknown and insignificant Roman or Italian families. Increasing the number of consuls each year eliminated de facto the traditional annuality of the office and reduced its authority. The implicit consequence of these actions was a gradual devaluation of the consulship. The suffect consulship was therefore a powerful tool in the hands of the triumvirs for strengthening their political position, weakening the old aristocracy and giving birth to a new elite based more firmly on personal loyalties.